1983
DOI: 10.1203/00006450-198304000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Receptors during Development in the Rat. I. TRH Binding Capacity

Abstract: SummaryIn order to study the role of thyroid releasing hormone (TRH) in the control of thyroid stimulating hormone (TSH) secretion during the neonatal period, we measured the binding of [3H]-TRH to pituitary homogenate of rats at various stages of development. In 2-day-old animals, the number of l3H]-TRH binding sites were similar to that of adult male animals (23 + 8 fmole/mg protein versus 21 + 7 fmole/mg protein, respectively). Between 5-21 days of age, the number of i3HJ-TRH binding sites was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In a recent study with the use of in situ hybridization histochemistry, a highly sensitive and anatomically specific form of analysis, TRH mRNA was seen in other brain regions prior to EI6 but TRH localized in the PVN was first detected at E 16 [5]. Once present, immunoreactive TRH levels in hypothalami increase until 18 days after birth [17] or young adulthood [6] as did TRH mRNA levels in the PVN [5]. In the present study, TRH mRNA was noted in the PVN at E l6, levels increased until 7d after birth and appeared to plateau through young adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study with the use of in situ hybridization histochemistry, a highly sensitive and anatomically specific form of analysis, TRH mRNA was seen in other brain regions prior to EI6 but TRH localized in the PVN was first detected at E 16 [5]. Once present, immunoreactive TRH levels in hypothalami increase until 18 days after birth [17] or young adulthood [6] as did TRH mRNA levels in the PVN [5]. In the present study, TRH mRNA was noted in the PVN at E l6, levels increased until 7d after birth and appeared to plateau through young adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…TRH administered to newborn euthyroid [8,9] and hypo thyroid rats [10] stimulates TSH secretion and this response in creases at 5-10 days after birth [8][9][10]. Also, TRH receptors have been described in the pituitary as early as 2 days after birth [17,19). Therefore, the presence of thyrotroph receptors for TRH as well as the ability of the thyrotroph to respond to exoge nous TRH supports the concept that the lack of TSH response to endogenous TRH in the early perinatal period is hypotha lamic rather than pituitary in origin.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the low circulating levels of thyroid hormones -Tt and Tj -in old rats may also contribute to the increased density ofTRH receptors, since Tj is known to exert an inhibitory control on pituitary TRH receptors [10, 31]. Indeed, in the developing rat, a progressive decrease in the density of pituitary TRH receptors is observed [3,16] which is concomitant with increases in plasma T3 and hypo thalamic TRH concentrations [35,41].As regards TRH in the anterior pituitary gland, our fin ding of an increased concentration of the peptide in old rats may appear unexpected in view of the reduced level ofTRH detected in the median eminence. However, it may reflect a greater internalization ofTRH in pituitary cells secondary to the increased number of pituitary receptors for TRH found in old animals.…”
mentioning
confidence: 99%
“…Previous studies have shown that TRH receptors are also expressed at birth and that their density increases postnatally (41,42). Concurrently, the number of TRH-producing neurons in the paraventricular nucleus increases during the first week of life (43,44).…”
Section: Discussionmentioning
confidence: 93%